Federated States of Micronesia : 2012 Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2013)
This statistical appendix paper for the Federated States of Micronesia (FSM) was prepared as background documentation for the periodic consultation with the member country, during the period 2004-11. This paper is based on the information available at the time it was completed on December 20, 2012. It is prepared to assist the authorities in fulfilling their obligations under the amended Compact Agreement. It contains numerous tables of basic data, GDP, several indices, and International Investment Position.